2021
DOI: 10.3889/oamjms.2021.7007
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Usage and Awareness among MedicalStudents: A Survey Study

Abstract: BACKGROUND: In the era of increasingly expanding digital ecosystem, health misinformation became highly risky, especially the information sources which are non-evidence based. This problem is magnified due to the vulnerability of most internet users, especially the adolescents information seekers who lack health literacy. AIM: The aim of this study is to explore the pattern of digital health usage among medical university students and their level of awareness towards choosing online health information (OHI). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This discovery is hardly surprising given the swift rise in mobile phone ownership and usage worldwide, including in Pakistan. 20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This discovery is hardly surprising given the swift rise in mobile phone ownership and usage worldwide, including in Pakistan. 20 …”
Section: Discussionmentioning
confidence: 99%
“…This discovery is hardly surprising given the swift rise in mobile phone ownership and usage worldwide, including in Pakistan. 20 The internet is rapidly becoming the primary source of students seeking health information. 21,22 Like previous studies of medical students, study results also indicated searching for information related to health and illness as the most frequent purpose of internet use (91%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical students use internet regularly, with a propensity for mobile devices, social networking, and text messaging. Although health information seeking is one of their primary purposes [7], yet they usually do not depend on quality criteria when choosing online health information sources. The choice of some users can sometimes be based on the design and the quality of pictures [8].…”
Section: Introductionmentioning
confidence: 99%